Hybridization of pedagogical models in Physical Education: Influence on the acquisition of competencies in the physical capacity of strength and enjoyment in students - Garcia-Monton, Marc; Beltran-Valls, M. R.; Monteagudo Chiner, Pablo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Although the benefits of strength training in adolescents are well-known, this fitness component is surrounded by certain myths that difficult its introduction in the educational setting. The hybridization of pedagogical models (PM) can be a useful tool to promote healthy habits through physical education (PE) while promoting secondary school students’ enjoyment. This longitudinal and quasi-experimental study of one group aimed to analyze the effectiveness of a CrossFit Teaching-Learning Sequence (SE-A) based on the hybridization of PM in 2nd year of secondary school students on the acquisition of skills linked to strength and enjoyment. Before and after the SE-A, 57 students (23 girls) were evaluated on knowledge of strength-related myths (ad-hoc questionnaire), and students’ enjoyment during physical education (with the PACES questionnaire). The results showed significant differences with higher scores after the SE-A regarding the myths questionnaire (p<0.001; Z=4.150; g Hedges=0.870) and the enjoyment in PE (p<0.001; Z=3.834; g Hedges= 0.351). The hybridization of PM seems to have a positive influence on the recognition of myths related to the strength and enjoyment of PE students. This aspect could increase physical activity levels in the short and/or long term in this age-group.